Raising the flag among the ruins: the crisis as helping hand for opposition parties?. (15th April 2019) - Conti, Nicolò; Pedrazzani, Andrea; Russo, Federico
Abstract: Within the context of the economic downturn in southern Eurozone countries and the imposition of new constraints on national policy-making, this article examines the congruence between party issue prioritization, during and after the electoral phase. This is done through a longitudinal analysis of four countries (Greece, Italy, Portugal, and Spain) and use of party manifesto and parliamentary question data. We found that between the electoral and parliamentary arenas, parties tend to emphasize different issues. However, this occurs in different ways across time, countries, and parties. We propose a measurement of issue congruence in agenda framing between the pre- and post-electoral phases to assess to what extent elections provide a guide for public policies. Moreover, we propose arguments to explain different results in the analyzed countries and across parties. We show that the crisis magnified the capacity of the opposition to maintain programmatic coherence – a helping hand for opposition parties (including the radical ones) that succeeded in boosting the relevance of their signature issues.